Conservation of Living Heritage: Elements in Conserving Portuguese Community’ Cultural Heritage - Jamaludin, Intan Syafinar; Seow, Ta Wee; Mat Radzuan, Indera Syahrul (Journal of Social Transformation and Regional Development, 2021)
Rapid urban development in today’s cities poses significant threats to heritage site with deterioration and destruction to the heritage by introduced pollution, political war, growing tourism activities, and natural disaster. The concern for the safeguarding of heritage materials and intangible assets has begun with a series of conservation practice that begins with material conservation, values conservation and living conservation approaches. Conservation of living heritage is by emphasizing the role of core community living in traditional settlement inside heritage area. The city of Melaka was declared as World Heritage Site in 2008 and the living heritage in the traditional village of Portuguese Settlement risking with the extinction of cultural heritage in the future due to insufficient cultural heritage conservation management. The purpose of this article is to highlight the conservation elements being used to conserve living heritage particularly for living heritage community. This article was conducted using qualitative research, by using literature and document analysis on relevant literatures, reports and standards. The result revealed the main factors contributed in conserving the living heritage came from elements of community participation, awareness, good communication, capacity building, and stakeholders’ involvement. The findings indicated that strong relationship among the elements will build a sustainable community within the heritage site particularly for the core community and at the same time conserving its heritage value.